The developing child - Bee, Helen L. (San Francisco : Harper & Row, 1981)
This edition has been revised to include increased coverage of the role of culture in development and expanded coverage of biological explanations and theories of development. There is also increased emphasis on emotional development.
Includes bibliographies and index.
Keywords: Child psychology; Child development